2000
DOI: 10.1053/joms.2000.8204
|View full text |Cite
|
Sign up to set email alerts
|

Late mandibular fracture after third molar surgery: A survey of Connecticut oral and maxillofacial surgeons

Abstract: Purpose: This study investigated the incidence and causative factors involved in late mandibular fractures after third molar surgery. Materials and Methods: A questionnaire was sent to 106 oral and maxillofacial surgeons in Connecticut, asking them about their experience with late fractures over a 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
81
1
14

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(100 citation statements)
references
References 8 publications
4
81
1
14
Order By: Relevance
“…Should the mode of anesthesia for surgery not influence mandibular fractures, the type of impaction seems to be significant. Similar to the findings of Krimmel and Reinert 5 and Perry and Goldberg, 7 We found a greater incidence of mandibular fracture with full bony impactions, presumably because a greater volume of bone is necessary for removal. Similar to other investigators' 5-7,9 we found that patient age is an important factor in fracture risk.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Should the mode of anesthesia for surgery not influence mandibular fractures, the type of impaction seems to be significant. Similar to the findings of Krimmel and Reinert 5 and Perry and Goldberg, 7 We found a greater incidence of mandibular fracture with full bony impactions, presumably because a greater volume of bone is necessary for removal. Similar to other investigators' 5-7,9 we found that patient age is an important factor in fracture risk.…”
Section: Discussionsupporting
confidence: 89%
“…The present study, in which we obtained an incidence of 0.0049%, confirms the conclusion of Perry and Goldberg. 7 Intraoperative fractures may occur with improper instrumentation and excessive force to the bone. This confirms the importance of tooth sectioning before extraction, but it cannot account for all of the complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The role of the OAC is 'intended to be illustrative of the characteristics of areas in terms of their demographic structure, household composition, housing, socio-economic characteristics and employment patterns'. 3 As a result, according to the 2013 survey, 22% of 'hard pressed living' children at the age of five in England, Wales and Northern Ireland have severe or extensive dental decay, compared with 18% of 'constrained city dwellers' children aged five, 9% 'suburbanites' and 9% 'urbanites' children aged five. 4 While a glossary of each of these groups are included in the technical report 2 we query the empirical utility of these classifications.…”
mentioning
confidence: 99%
“…3 Nevertheless, how we define and measure health is a political act, influencing public opinion of health and health policy more generally. 5 By using the OAC classifications the distribution of child oral health is recorded not according to social class but rather to these 'fuzzy' descriptive classifications.…”
mentioning
confidence: 99%